The Role of the Regional Tax and Retribution Management Agency in Controlling Tax Avoidance in Land Sale Transactions in Sorong Regency - Syam, Sri Juliana; Aldilla Yulia Wiellys Sutikno; Mariya Azis; Adi Randi M. Rajab (Equality Before The Law, 2025)
This study aims to determine the role of the Regional Tax and Retribution Management Agency in controlling tax avoidance in land sale and purchase transactions, especially related to Land and Building Acquisition Fees in Sorong Regency. This study uses a socio-legal research and legislation approach (Statute Approach) by analyzing and understanding the hierarchy of legislation and how the law operates in real life, not only from a normative perspective but also empirically. This study shows that BP2RD has an important responsibility in ensuring taxpayer compliance through field verification before the issuance of the BPHTB sheet letter. However, in reality, tax avoidance still occurs due to lack of supervision from BP2RD. The results of this study are expected to provide insight for local governments in improving supervision and enforcement of regulations related to BPHTB in order to maximize state cash receipts from the tax sector.